Design and Build the Game "Mickey Adventure Saves his Friend from Monsters" Using the Finite State Machine Method - Muchamat David Arifudin; Cindy Taurusta; S Suprianto (SAGA: Journal of Technology and Information System, 2025)
Several years ago during the pandemic, people tended to experience high levels of stress because they thought the corona virus was a dangerous virus, causing psychological impacts in the form of fear, anxiety, and stress .To reduce stress due to the pandemic, people anticipated it by playing games. So with this the author wants to make a game with the Adventure genre is a good solution in relieving stress during a pandemic besides that adventure games are games that are easily understood by all groups from children to adults. Besides relieving stress, Adventure games can train patience and decision making.